Accreta placentation: a systematic review of prenatal ultrasound imaging and grading of villous invasiveness. - Jauniaux, E; Collins, S; Jurkovic, D; Burton, G (Elsevier, 2016)
Determining the depth of villous invasiveness before delivery is pivotal in planning individual management of placenta accreta. We have evaluated the value of various ultrasound signs proposed in the international literature for the prenatal diagnosis of accreta placentation and assessment of the depth of villous invasiveness.We undertook a PubMed and MEDLINE search of the relevant studies published from the first prenatal ultrasound description of placenta accreta in 1982 through March 30, 2016, using key words "placenta accreta," "placenta increta," "placenta percreta," "abnormally invasive placenta," "morbidly adherent placenta," and "placenta adhesive disorder" as related to "sonography," "ultrasound diagnosis," "prenatal diagnosis," "gray-scale imaging," "3-dimensional ultrasound", and "color Doppler imaging."The primary eligibility criteria were articles that correlated prenatal ultrasound imaging with pregnancy outcome. A total of 84 studies, including 31 case reports describing 38 cases of placenta accreta and 53 series describing 1078 cases were analyzed. Placenta accreta was subdivided into placenta creta to describe superficially adherent placentation and placenta increta and placenta percreta to describe invasive placentation.Of the 53 study series, 23 did not provide data on the depth of villous myometrial invasion on ultrasound imaging or at delivery. Detailed correlations between ultrasound findings and placenta accreta grading were found in 72 cases. A loss of clear zone (62.1%) and the presence of bridging vessels (71.4%) were the most common ultrasound signs in cases of placenta creta. In placenta increta, a loss of clear zone (84.6%) and subplacental hypervascularity (60%) were the most common ultrasound signs, whereas placental lacunae (82.4%) and subplacental hypervascularity (54.5%) were the most common ultrasound signs in placenta percreta. No ultrasound sign or a combination of ultrasound signs were specific of the depth of accreta placentation.The wide heterogeneity in terminology used to describe the grades of accreta placentation and differences in study design limits the evaluation of the accuracy of ultrasound imaging in the screening and diagnosis of placenta accreta. This review emphasizes the need for further prospective studies using a standardized evidence-based approach including a systematic correlation between ultrasound signs of placenta accreta and detailed clinical and pathologic examinations at delivery.